New 2,2-diphenylpropane and ethoxylated aromatic monoterpenes from Lavandula gibsoni (Lamiaceae) - Kulkarni, Roshan R.; Joshi, Swati P. (Natural Product Research, 2013)
A new substituted 2,2-diphenylpropane (1) and two new ethoxylated aromatic monoterpene alcohols (2 and 4) have been isolated from the acetone extract of the aerial parts of Lavandula gibsoni, along with the known compounds 8-hydroxycarvacrol (3), 8-hydroxythymol (5), coumarin (6), 4-methylresorcinol (7), 7,4-dimethylapigenin (8), salvigenin (9), -sitosteryl-3-O–D-glucopyranosyl-6-O-palmitate (10) and euscaphic acid D (11). The structures of the isolated compounds were assigned on the basis of their H-1- and C-13-NMR spectra and two-dimensional NMR techniques, which included COSY, HSQC, HMBC and NOESY experiments and comparison with the reported literature.
Keywords: 2; 2-diphenylpropane; aromatic monoterpene alcohols; Lamiaceae; Lavandula gibsoni

New pimarane diterpenes and other antimycobacterial metabolites from anisochilus verticillatus - Kulkarni, Roshan R.; Shurpali, Ketaki; Khedkar, Vijay M.; Puranik, Vedavati G.; Sarkar, Dhiman; Joshi, Swati P. (Natural Product Research, 2016)
Phytochemical investigation of the acetone extract of the aerial parts of Anisochilus verticillatus afforded a new 8,9-secopimarane diterpene (1), two new isopimarane diterpenes (2, 3) and the known ursolic acid (4), beta-amyrin (5), -amyrin (6), stigmast-5-en-3-one (7) and hydroxychavicol (8). Structures of the new compounds were elucidated with the help of 1D and 2D nuclear magnetic resonance spectroscopic data, and single crystal X-ray crystallography of compound 3. Compounds 2 and 8 inhibited Mycobacterium tuberculosis H37Ra with an IC50 of 11.3 (IC90 of 20.0g/mL) and 12.5g/mL, respectively. Correspondingly, molecular docking studies with Extra Precision Glide revealed a correlation between score and biological activity for these compounds to describe the molecular basis for the most significant SAR results.
Keywords: alanine racemase; Anisochilus verticillatus; antimycobacterial activity; diterpenes; Lamiaceae